Chasing the conventionality thesis - Arena, Federico (EUNOMÍA. Revista en Cultura de la Legalidad, 2014)
The author offers a statement of legal conventionalism, i.e., the point of view that holds the conventionality thesis about law. According to that thesis the fundamental legal fact is (determined by) a convention. In order to flesh out the thesis the author proposes, following the work of other philosophers, to distinguish, first, between two notions of convention, i.e., agreement based and non-agreement based conventions; second, between different levels of conventionality; and third, between two types of conventions, to wit, coordination conventions that solve a recurrent coordination problem and constitutive conventions that define a practice and determine how to be part of it. On this basis the author analyzes and criticizes the traditional versions of the conventionality thesis that tried to give an account of the hartian rule of recognition. In order to overcome the difficulties of previous versions, the author proposes a revision of the conventionality thesis based on a distinction between two phases within the practice of the identification of law. On the one hand, the identification of legal text conceived as a coordination convention and, on the other hand, the practice of the interpretation of legal texts, conceived as a set of constitutive conventions.